The harbor of microorganism on used toothbrushes Kandungan organisme mikro pada sikat gigi yang telah digunakan - Asmawati Asmawati (DiscoverSys Inc., 2011)
The purpose of this study was to evaluate the microorganisms found on used toothbrushes. In this study 25toothbrushes were investigated, 10 toothbrushes were used less than 3 months, 10 toothbrushes have been used for3-6 months, and 5 toothbrushes have been used for more than 6 months. Some gram-positive coccus, such asStaphylococcus, Streptococcus and Diplococcus. The results showed there were microbial harbored of usedtoothbrushes. Toothbrushes that have been used for 6 months were harbored more microorganisms than thetoothbrushes that have been used less than 3 months and 3-6 months. It can be concluded that the longer using timeof toothbrush the more increase of microorganism amount found on toothbrush.